The Impacts Of Financial Management, Social Network, Platform And The Mediation Of Business Intelligence On The Performance Of Equity Crowdfunding Funded Firms In Malaysia - Siti Fatimah binti Mohd Kassim (Universiti Sains Islam Malaysia, 2024)
Matric:4150163 (FEM)